Development of Epitaxial Thin Film Model Electrodes for the Systematic Investigation of Metal Exsolution from MIEC Perovskite Oxides. (10th July 2019) - Weber, Moritz Lukas; Ma, Qianli; Meuffels, Paul; Hensling, Felix V. E.; Lenser, Christian; Gunkel, Felix; Menzler, Norbert H.; Dittmann, Regina; Waser, Rainer; Guillon, Olivier
Abstract : Metal exsolution of catalytically active B-site dopants of mixed ion and electron conducting (MIEC) perovskites under reducing conditions can be utilized for the preparation of high-performance electrode materials. To study the underlying mechanisms of the exsolution process with respect to specific material aspects - for example structural properties of the host lattice - advanced model systems with well-defined properties are required. Pulsed laser deposition (PLD), enables the fabrication of such model electrode systems by epitaxial growth of complex oxides with highly defined and tunable structural properties. In this study, we present the development of epitaxial model electrodes of Nb and Ni co-doped strontium titanate (SrTi0.9 Nb0.05 Ni0.05 O3-δ, STNNi) by PLD. We discuss epitaxial growth and material properties providing well-defined thin film model electrodes suitable for the investigation of nanoparticle exsolution.